Wanprestasi/Perbuatan Melawan Hukum Ahli Waris Pengganti Dalam Perjanjian Kredit Perbankan - Purnama, Rendika; Abdallah, Raffi Ikzaaz; Ramadhon, Daffa Charisma Putra; Febrian, Matthew; Mahardika, Agus; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bank credit agreements are legally binding arrangements between debtors and creditors, including when the debtor passes away. In such cases, legal responsibility for the outstanding debt may be transferred to the substitute heirs. This study aims to examine the legal liability of substitute heirs in bank credit agreements and analyze acts of default or unlawful conduct that may arise when obligations are not fulfilled. The research employs a normative legal method with a descriptive approach and juridical analysis of legislation, jurisprudence, and legal doctrines. The results show that substitute heirs bear limited liability based on the portion of inheritance received. However, in practice, breaches of obligation often occur, either due to ignorance or intentional neglect, resulting in legal consequences that harm the bank as creditor. Therefore, strengthening regulations and educating the public on the legal responsibilities of heirs are essential to ensuring legal certainty and balanced protection for all parties in the banking system.